ITOC2 – 037. CEA TCB, A novel T-cell bispecific antibody with potent in vitro and in vivo antitumour activity against solid tumours. (March 2015) - Bacac, Marina; Fauti, Tanja; Colombetti, Sara; Sam, Johannes; Nicolini, Valeria; Steinhoff, Nathalie; Ast, Oliver; Bruenker, Peter; Hosse, Ralf; Hofer, Thomas; Moessner, Ekkehard; Jaeger, Christiane; et al.
Abstract : T cell bispecific antibodies (TCBs) are potent molecules that upon simultaneous binding to tumour cells and T cells trigger strong T cell activation resulting in the killing of tumour cells. CEA TCB (RG7813) is a novel bispecific antibody targeting carcinoembryonic antigen (CEA), often overexpressed on solid tumours (e.g. colorectal, gastric, pancreatic, lung carcinoma etc.), and the CD3 epsilon chain present on T cells. CEA TCB bears several innovative technological features that distinguish it from other bispecific antibodies currently in (pre-)clinical development: (a) bivalency for tumour antigen translating into higher avidity, superior potency and better differentiation between high and low antigen-expressing cells; (b) head-to-tail fusion geometry for anti-tumour and CD3-binding domains, resulting in higher potency compared to conventional IgG-based TCBs; (c) extended half-life compared to non-Fc-based TCBs; (d) fully silent Fc ensuring lower risk of FcgR-mediated infusion reactions; and (e) robust production using standard manufacturing processes (enabled by "CrossMAb" and knob-into-hole bispecific antibody technologies). In vitro, CEA TCB mediates potent target-dependent T cell cytotoxicity, T cell activation, proliferation, and cytokine release in killing assays, exclusively in the presence of CEA-expressing target-cells. CEA TCB activity correlates with CEA expression level, showing higher potency against tumour cells with high expression of CEA. In vivo, CEA TCB induces dose- and time-dependent regression of CEA-expressing tumours with variable amounts of immune cell infiltrate. In fully humanised NOG mice, CEA TCB is efficacious in poorly-infiltrated tumours and converts non-inflamed into highly-inflamed tumours. Histological and FACS analyses revealed that CEA TCB recruits new T cells into tumours and/or expands pre-existing ones and is able to induce T cell re-localisation from the tumour periphery into the tumour bed. Surprisingly, CEA TCB treatment also qualitatively alters the composition of intratumoural T cells resulting in an increased frequency of activated (CD69, CD25), proliferating (Ki67) and differentiated T cells (having effector memory phenotype) that are ready to kill (express high levels of Granzyme B). Taken together, these preclinical data show that CEA TCB is a novel tumour-targeted T cell bispecific antibody with promising anti-tumour activity and the novel ability to modify the tumour microenvironment. Phase 1 clinical trials with CEA TCB are currently ongoing. Future studies will focus on identification of combination partners that inhibit T cell suppression and unleash the full potential of T cell activity. Presented in Plenary Session 4 : Immunomodulatory agents.